Preparation Of Ferrocene Derivatives Of Niobium IV - Abdulla, A.W.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included the preparation of the dihalogens -1,3 metalla-2[3] ferrocenophanes like Cp2NbS2Fc,(tBuCp)2NbS2Fc,Cp2NbSe2Fc and (tBuCp)2NbSe2Fe where (Fc=ferrocence) These complexes has been prepared from the reaction of (R)2 NbCl2 with FCLiM2 , where(R=Cp,tBuCp) (M = S,Se) under refluxing in toluene,the reaction was carried under Argon atmosphere . These complexes were characterized by elemental microanalysis ,Masse spectra scopy, nuclear magnetic resonance (1HNMR) and melting points .